2017
DOI: 10.1159/000471917
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Associated Lactic Acidosis Undergoing Renal Replacement Therapy in Intensive Care Units: A Five-Million Population-Based Study in the North-West of Italy

Abstract: Background: Metformin-associated lactic acidosis (MALA) is a severe complication of drug administration with significant morbidity and mortality. So far no study in large population areas have examined the incidence, clinical profile and outcome of acute kidney injury (AKI)-MALA patients admitted in intensive care units (ICUs) and treated by renal replacement therapy (MALA-RRT). Methods: Retrospective analysis over a 6-year period (2010-2015) in Piedmont and Aosta Valley regions (5,305,940 inhabitants, 141,174… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 29 publications
3
46
1
5
Order By: Relevance
“…The overall mortality of 40% in our study is in line with the mortality reported in previous studies, ranging from 20 to 50% [7,8,[12][13][14][17][18][19][20][21]. Blood pH, lactate, creatinine, and serum metformin concentration in the ECTR group in this study are similar to that reported in the literature [9,13,[20][21][22]. The significantly higher lactate and creatinine concentrations in the ECTR group compared to the non-ECTR group have also been reported in other studies [9,12,19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall mortality of 40% in our study is in line with the mortality reported in previous studies, ranging from 20 to 50% [7,8,[12][13][14][17][18][19][20][21]. Blood pH, lactate, creatinine, and serum metformin concentration in the ECTR group in this study are similar to that reported in the literature [9,13,[20][21][22]. The significantly higher lactate and creatinine concentrations in the ECTR group compared to the non-ECTR group have also been reported in other studies [9,12,19].…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of MALA varies from 0 to 138 per 100.000 patient years and may increase in the coming years due to the increase in the number of type 2 diabetes mellitus patients and the use of metformin [4,6,8,9]. Several studies suggest that starting timely treatment might reduce MALA-related morbidity and mortality [8][9][10][11][12][13][14]. Extracorporeal treatments (ECTRs) may be necessary to remove metformin, clear lactate, and correct acid-base abnormalities [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin reduces glucose levels by increasing insulin sensitivity, reducing hepatic glucose release and increasing muscle uptake [1] [2]. It prevents hepatic gluconeogenesis by reducing the lactate reuptake.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Metformin is one of the first-line treatments for patients with type 2 diabetes mellitus [1]. Metformin reduces the risk of mortality and morbidity in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation